2012
DOI: 10.1590/s0103-50532012000400019
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive investigation of the mineral composition of brazilian bee pollen: geographic and seasonal variations and contribution to human diet

Abstract: A composição de minerais foi investigada em 154 amostras de pólen apícola, provenientes de diferentes regiões do Brasil. A técnica de ICP OES foi utilizada para determinar Ca, Cu, Fe, K, Mg, Mn, Na, P, Se e Zn, após mineralização em sistema de microondas. Utilizando parâmetros instrumentais otimizados conseguiu-se boa exatidão e precisão na determinação simultânea dos minerais. Em geral, as amostras dos estados do Nordeste apresentaram teores de minerais mais elevados e produção constante durante o ano. Os min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 13 publications
3
47
3
2
Order By: Relevance
“…These ranges are similar to those obtained by Stanciu et al (2012) for K, Mn, Zn, and Cu. Meanwhile, Na, Ca, Mg, and Fe tended to be higher than those obtained by Carpes et al (2009) and Morgano et al (2012). The differences among our values and the values found in other countries might be correlated to the plant growth conditions, such as: soil, irrigation water, and geographic origin.…”
contrasting
confidence: 81%
See 2 more Smart Citations
“…These ranges are similar to those obtained by Stanciu et al (2012) for K, Mn, Zn, and Cu. Meanwhile, Na, Ca, Mg, and Fe tended to be higher than those obtained by Carpes et al (2009) and Morgano et al (2012). The differences among our values and the values found in other countries might be correlated to the plant growth conditions, such as: soil, irrigation water, and geographic origin.…”
contrasting
confidence: 81%
“…Honeybee-collected pollen provides a rich source of easily digestible protein (Crailsheim et al, 1992;Campos et al, 1996;Serra Bonvehi and Escola Jorda, 1997;Szczęsna, 2006a;b). In addition to proteins, pollen also contains carbohydrates, fats and minerals (Orzáez Villanueva et al, 2002;Szczęsna et al, 2002;Almeida-Muradian et al, 2005;Human and Nicolson, 2006;Szczęsna, 2006a;2007;Campos et al, 2008;Carpes et al, 2009;Martins et al, 2011;Morgano et al, 2012). The chemical composition of bee-pollen showed an average of 7.40% moisture, 20.00% protein, 6.00% lipids, and 2.20% ash (Almeida-Muradian et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis showed significant difference in mineral content among samples, even among the 3 samples (B, C and D) collected at the same apiary. The levels of minerals may vary according to geographical and botanical origin of pollen grains (Szczêsna, 2007;Carpes et al, 2009;Morgano et al, 2012;Taha, 2015); therefore, pollen in samples collected at the same apiary may have been harvested from different flowers over the sampling period.…”
Section: Mineral Compositionmentioning
confidence: 99%
“…In this study, all 5 bee pollen samples fell into the "high content food" class and can be used as dietary sources of P by both men and women between 19 and 30 years (Brasil, 2005(Brasil, , 2012. Carpes et al (2009) have reported P contents in samples collected in Rio Grande do Sul State (Brazil) ranging from 565 and 846 mg/100 g. In a more comprehensive study using bee pollen samples from twelve Brazilian States, including Rio Grande do Sul State, Morgano et al (2012) have observed P contents between 218 and 816 mg/100 g. All samples in this study met the standard for P content (between 80 and 600 mg/100 g) set by the International Honey Comission (IHC) (Campos et al, 2008). Carpes et al (2009) for samples collected in Rio Grande do Sul State (54.0-214.9 mg/100 g); however, they were lower than the average content (183.8 mg/100 g) reported for samples from the same state analyzed by Morgano et al (2012).…”
Section: Mineral Compositionmentioning
confidence: 99%